Assessing Risk Factors of Pneumonia among Adults at Ibn-Sina in Mosul City - Sana Thanoon Ahmed, (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: the aim of the study to assess the most common risk factors of pneumonia at adult and find thesocio-demographic characteristics of sample.Methodology: the study performed at Ibn-Sina teaching hospital (intensive care unit) and out patient in the samehospital period of (15 ) November (2006) till (1ا٤) February (2007).The sample of the study includes (65)patients with pneumonia for different underlying causes who were attending Ibn-Sina teaching hospital agerange (59-68) years is the highest level and is the most common risk factor for pneumonia.Results: the results of the study most patients' hospital acquired-pneumonia from contamination duringadministration to hospital but community acquired-pneumonia were difficult in swelling, bad cleaning of mouthand smoking.Recommendations: This study recommends providing pneumococcal pneumonia vaccine for adult those at riskfor serious pneumonia and should be revaccinated every six years.